ANALISIS PENGARUH MOTIVASI, LINGKUNGAN DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT. PDAM - M. Abduh Idris; Muh. Rezky Naim (JURNAL LENTERA BISNIS, 2023)
The author conducted a study entitled The Influence of Motivation, Environment and Work Morale on Employee Performance at PT. PDAM Majene Regency In this study, the authors proposed a construction problem related to the influence of work motivation on employee performance at PT. PDAM Majene Regency, How the Work Environment Affects Employee Performance at PT. PDAM Majene Regency, How Workplace Morale Affects Employee Performance at PT. PDAM Majene Regency and what motivational, environmental, and moral factors have the most influence on employee performance at PT. PDAM. The population is not too large, so the sampling technique that will be used in this study is a saturated sampling technique with a sample of 20 respondents, while the sampling technique using the tools used in the study must be tested for reliability and validation. And multiple linear regression, partial significance test (t-test), and concurrent significance test (f test) were included simultaneously in the regression model for the dependent variable tested at an average significance level of 0.05. Regarding the results that the author can convey after researching the effect of motivation, environment, and morale on employee performance, the following conclusions can be drawn: employees influence employee performance, influence employee morale on employee performance and motivation, employee environment and enthusiasm simultaneously or jointly affect the performance of f employees at PT. PDAM Majene Regency.Keywords: Motivation, Environment, Morale, Employee Performance